2021
DOI: 10.3390/ph14100985
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovering Psilocybin as an Antidepressive Treatment Strategy

Abstract: There has recently been a renewal of interest in psychedelic research on the use of psilocybin in psychiatric treatment and, in particular, for the treatment of major depressive disorder (MDD). Several state-of-the-art studies have provided new insight into the mechanisms of action of psilocybin and its therapeutic potential. Nevertheless, many questions remain unanswered. With this review, we provide an overview of the current state of research on the potential mechanisms of psilocybin, its antidepressant pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 94 publications
0
4
0
2
Order By: Relevance
“…Interestingly, a clear pattern emerged for past use of psychedelics—the higher the proportion of study participants who had used psychedelics in the past, the higher the post-psilocybin treatment effect observed. Past use of psychedelics has been proposed to create an expectancy bias among participants and amplify the positive effects of psilocybin 82 83 84 ; however, this important finding has not been examined in other meta-analyses and may highlight the role of expectancy in psilocybin research.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a clear pattern emerged for past use of psychedelics—the higher the proportion of study participants who had used psychedelics in the past, the higher the post-psilocybin treatment effect observed. Past use of psychedelics has been proposed to create an expectancy bias among participants and amplify the positive effects of psilocybin 82 83 84 ; however, this important finding has not been examined in other meta-analyses and may highlight the role of expectancy in psilocybin research.…”
Section: Discussionmentioning
confidence: 99%
“…Although the safety and efficacy of psilocybin as an antidepressant are the focus of most recent clinical trials (more than 100 clinical trials have been registered), there are still no definitive data that can establish whether psilocybin can offer substantial clinical improvement over existing antidepressant therapies [ 200 , 201 ]. It has recently been reported that the antidepressant response of psilocybin is not statistically stronger than the conventional antidepressant escitalopram [ 202 ].…”
Section: Psilocybe Cubensismentioning
confidence: 99%
“…On the other hand, psilocybin's effects at the 5HT receptors are responsible for decreased depression and suicidal behaviors, as well as increased memory and learning [11]. Further, it is believed that psilocin's activation of the 5HT-2A receptor is responsible for increased release of dopamine from the striatum, which is capable of regulating the defective reward pathway in patients who suffer from depression and with suicidal ideation [6].…”
Section: Review Mechanism Of Actionmentioning
confidence: 99%